2014
DOI: 10.1007/s12011-014-0093-6
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Region Differences and Age-Related Changes in Copper, Zinc, and Manganese Levels in the Human Brain

Abstract: Using inductively coupled plasma-mass spectrometry after samples microwave-assisted acid digestion, zinc (Zn), copper (Cu), and manganese (Mn) levels were measured in 14 different areas of the human brain of adult individuals (n = 42; 71 ± 12, range 50-101 years old) without a known history of neurodegenerative, neurological, or psychiatric disorder. The main goals of the work were to establish the "normal" (reference) values for those elements in the human brain and to evaluate the age-related changes, a prio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 51 publications
9
27
0
1
Order By: Relevance
“…Whether or how the previously reported decrease in serum Zn levels in AD 55 is associated with altered brain-Zn regulation is unclear. A previous study has suggested that HP may contain the highest Zn content among those brain-regions examined: 17 consistently, we found Zn levels to be higher in HP than other regions, although they approximated those in CB.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Whether or how the previously reported decrease in serum Zn levels in AD 55 is associated with altered brain-Zn regulation is unclear. A previous study has suggested that HP may contain the highest Zn content among those brain-regions examined: 17 consistently, we found Zn levels to be higher in HP than other regions, although they approximated those in CB.…”
Section: Discussionsupporting
confidence: 82%
“…fresh or formalin-fixed), handling, numbers of samples, and intrinsic variation in the distribution of metals in the brain tissue, resulting perhaps from both compartmentalization and inter-regional differences. 7,16,17 Therefore, further mapping of the regional distribution of metals in the brain is required to substantiate and extend our understanding of the content of metals in various brain regions, and to associate these with region-specific variation in AD pathology. As one example, Cu, Fe and Zn are enriched in amyloid plaques from AD brain: 18,19 by contrast, measurement of levels of these metals in whole-brain tissue from affected regions has yielded somewhat inconsistent values.…”
Section: Introductionmentioning
confidence: 99%
“…3). This pattern was similar to that described for Cu in the human insular cortex (Dobrowolska et al 2008) and in agreement with previous reports indicating that Cu was more abundant in GM than WM in nonhuman primate brain (Bonilla et al 1984; Ramos et al 2014; Knauer et al 2017). Iron was observed in blood vessels, as expected due to its well-known association with hemoglobin, but also along layer IV and infragranular layers.…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, the increase in arginase activity after Mn-exposure in vivo is consistent with the increase of ARG2 protein; arginase is known to be stabilized in vitro by incorporation of Mn into each homomer [23]. Because the striatum exhibited more ARG2 than any other brain region, and because striatum normally accumulates Mn preferentially [14], the region may be especially vulnerable to Mn deficiency [24], though there is not a detectable difference in total striatal Mn levels between WT and YAC128Q at this stage [1]. The reduction in arginase enzyme activity in this HD model therefore suggests a specific cellular or subcellular deficit in Mn bioavailability for this enzyme.…”
Section: Discussionmentioning
confidence: 84%